PENGEMBANGAN STRATEGI PEMASARAN BAWANG GORENGPADA INDUSTRI âMUSTIKAâ KECAMATAN PALU BARAT DI KOTA PALU - Lestari, Murti Suci; Mappatoba, Marhawati; Lamusa, Arifuddin (AGROTEKBIS, 2018)
This study aims to identify internal and external environment factors, formulating of marketing strategies using SWOT analysis. The study was conducted in